Is there a Learning Crisis in Punjab? : Initial Data Release from the SABER SD Survey - Geven, Koen Martijn (World Bank, Washington, DC, 2021)
In 2018, the World Bank released World Development Report which showed that the world is facing a ‘Learning Crisis’. Following up from that report, the Bank has launched the Human Capital Project to mobilize more resources, including for the improvement of learning outcomes. Subsequently, global leaders have been increasingly focused on solving this learning crisis and have renewed attention for Sustainable Development Goal 4: Quality Education. Pakistan is an early adopter of this Human Capital Project, and the new government is taking the lead to address the root causes of the learning crisis. This report aims to help the government with that agenda, by quantifying the extent of the learning crisis, and to highlight the main causes of the crisis. According the World Development Report, the ‘Learning Crisis’ consists of three main elements. The first is that access to schooling is still unequally distributed. While there have been huge efforts to expand schooling, there are still countries (including Pakistan) with millions of children out of school. Children living in regions with violence, children from poorer families and children with physical or mental disabilities are still often excluded. The second element is that even those who are in school are often not learning anything at all. In Malawi and Zambia, for instance, 89 percent of students could not read a single word by the end of Grade 2. In India, that figure is 85 percent. These numbers are important, as children who do not master basic literacy will probably never catch up with the curriculum. In other words, schooling is not necessarily the same as learning. The third element of the learning crisis is that the proximate causes of the learning crisis, low quality teaching, student school readiness, school leadership and school inputs, are not systematically addressed by actors in the system. One of the reasons behind this is that there is no systematic data collection on these factors.